Medial meniscus posterior root repair with concomitant centralization does not demonstrate superior reduction of meniscal extrusion or improved clinical outcomes compared with isolated repair: A systematic review and meta‐analysis - Angelo V. Vasiliadis; Nifon K. Gkekas; Alexandros Maris; Nicholas Colyvas; Michael Hantes (Knee Surgery, Sports Traumatology, Arthroscopy, 2026)
Abstract Purpose To evaluate whether the addition of a meniscal centralization procedure to medial meniscus posterior root (MMPR) repair improves medial meniscus extrusion (MME) and patient‐reported outcomes compared with isolated MMPR repair. Methods A systematic review and meta‐analysis were conducted in accordance with Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guidelines. PubMed, Cochrane CENTRAL and Scopus were searched from inception to 28 February 2026. Comparative studies evaluating isolated MMPR repair versus MMPR repair combined with centralization procedure (including transtibial pull‐out repair, posteromedial pull‐out repair with all‐inside sutures and anchor‐based techniques) and reporting radiographic extrusion measured by magnetic resonance imaging and/or patient‐reported outcomes were included. Effect estimates were calculated using change scores. Mean differences (MDs) were used for extrusion, and standardized mean differences (SMDs) were used for patient‐reported outcomes. Heterogeneity was assessed using the I 2 statistic, and pooled estimates were generated using a random‐effects model. Results Six comparative studies (one randomized controlled trial [RCT] and five retrospective cohort studies) comprising 309 patients (167 isolated repair; 142 centralization repair) with a mean follow‐up period of 11.2 months (range, 3–26.8 months) were included. Participants were predominantly female, with mean age of 50.3–66.4 years, body mass index of 22.5–29 kg/m 2 and Kellgren–Lawrence ≤ 2. The overall pooled analysis demonstrated no significant difference in MME reduction between centralization and isolated repair (MD 0.4 mm; 95% confidence interval [CI] −0.34 to 1.22; p = 0.27; I 2 = 89%). Although post‐operative MME was lower in the centralization group (3.3 vs. 3.8 mm), the absolute difference between groups was only 0.6 mm, suggesting limited clinical relevance. No significant differences were observed between groups in Lysholm ( p = 0.93), International Knee Documentation Committee ( p = 0.13) or visual analogue scale pain scores ( p = 0.10). Reporting of complications was inconsistent, with no conversions to total knee arthroplasty during follow‐up. Conclusions The addition of a meniscal centralization to MMPR repair does not demonstrate a consistent reduction in meniscal extrusion or improvement in patient‐reported outcomes compared with isolated MMPR repair. Given the heterogeneity of the current evidence and the predominance of non‐randomized studies, further high‐quality RCTs are required to clarify its clinical value. Level of Evidence Level II.